Adaptation of the Kirkstall QV600 LLI Microfluidics System for the Study of Gastrointestinal Absorption by Mass Spectrometry Imaging and LC-MS/MS - Chloe E. Spencer; Stephen Rumbelow; Steve Mellor; Catherine J. Duckett; Malcolm R. Clench (Pharmaceutics, 2022)
Absorption studies on oral drugs can be difficult due to the challenge of replicating the complex structure and environment of the GI tract. Drug absorption studies can be conducted using in vivo and ex vivo animal tissue or animal-free techniques. These studies typically involve the use of Caco-2 cells. However, Caco-2 cells do not incorporate all the cell types found in intestinal tissue and lack P450 metabolizing enzymes. The QV600 LLI system is a microfluidics system designed for use with cell culture. Here, it has been adapted to house appropriate sections of ex vivo porcine tissue to act as a system that models the duodenum section of the small intestine. A pH regulated solution of Atorvastatin was flowed over the apical layer of the GI tissue and a nutrient solution flowed over the basal layer of the tissue to maintain tissue viability. The tissue samples were snap-frozen, cryosectioned, and imaged using MALDI Mass Spectrometry Imaging (MSI). A proof-of-concept study on the effect of excipients on absorption was conducted. Different concentrations of the solubilizing agent were added to the donor circuit of the QV600 LLI. The amount of Atorvastatin in the acceptor circuit was determined to study the effect of the excipient on the amount of drug that had permeated through the tissue. Using these data, Papp, pig values were calculated and compared with the literature.